1997
DOI: 10.1182/blood.v89.10.3778.3778_3778_3786
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Analysis of Apoptotic Cell Death Using Proton Nuclear Magnetic Resonance Spectroscopy

Abstract: Quantification of apoptotic cell death in vivo has become treatment (r 2 ! .947, N ! 27 samples). There was also a direct temporal relationship between an increase in the CH 2 / an important area of investigation in patients with acute lymphoblastic leukemia (ALL). We have devised a noninva-CH 3 signal intensity ratio and the onset of apoptosis as detected by nuclear morphologic analysis, fluorescein-annexin sive analytical method to estimate the percentage of apoptotic lymphoblasts in doxorubicin-treated Jurk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
49
2

Year Published

2004
2004
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(56 citation statements)
references
References 33 publications
5
49
2
Order By: Relevance
“…Increases in the fatty acid signals at 0.89, 1.3, 1.58 and 2.2 ppm with longer exposure to cisplatin demonstrated the accumulation of -CH 3 , -CH 2 -CH 2 -CH 2 -, -CH 2 -CH 2 -C = O and -CH 2 -CH 2 -C = O moieties, respectively, arising from fatty acid chains, which could be saturated or unsaturated. Contrary to previous studies (19), the ratio of the signals CH 2 /-CH 3 did not increase significantly during treatment, implying that there is no substantial change in the mean chain length of the fatty acids. The difference Table 1.…”
Section: Discussioncontrasting
confidence: 99%
“…Increases in the fatty acid signals at 0.89, 1.3, 1.58 and 2.2 ppm with longer exposure to cisplatin demonstrated the accumulation of -CH 3 , -CH 2 -CH 2 -CH 2 -, -CH 2 -CH 2 -C = O and -CH 2 -CH 2 -C = O moieties, respectively, arising from fatty acid chains, which could be saturated or unsaturated. Contrary to previous studies (19), the ratio of the signals CH 2 /-CH 3 did not increase significantly during treatment, implying that there is no substantial change in the mean chain length of the fatty acids. The difference Table 1.…”
Section: Discussioncontrasting
confidence: 99%
“…Increases in 1 H MRS visible lipids have been observed following induction of apoptosis in many tumors (17,(40)(41)(42)(43)(44). While the lipid methyl and methylene peaks can increase as a result of necrosis as well as apoptosis, the PUFA peak increases only after apoptosis (41).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it has been shown that high-frequency ultrasound (18) measurements of back-scattered intensity can distinguish between normal and apoptotic cells in cell samples, tissue, and tumors. In particular, magnetic resonance spectroscopy (MRS) has demonstrated increased lipid mobility (19,20), which indicates the presence of lipid droplets, and increased choline levels (7), which indicates changes in glycolysis and in the phosphatidylcholine synthesis pathways. MRI diffusion shows promise in detecting the decreased cellularity and increased extracellular water content at late stages of apoptosis (12,13) and can indicate changes in cell membrane permeability (21).…”
mentioning
confidence: 99%